2017
DOI: 10.1002/hed.24874
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for wound complications in head and neck reconstruction: 773 free jejunal reconstruction procedures after total pharyngolaryngoesophagectomy

Abstract: Our findings suggest that use of an open drain, cardiovascular disease, and a longer operation time are significant risk factors for abscess formation, fistula formation, and cervical skin flap necrosis, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…Furthermore, the current findings were consistent with their results. Sugiyama et al [ 16 ] reported that the use of an open drain, cardiovascular disease, and longer operation time are significant risk factors for abscess formation, fistula formation, and cervical flap necrosis. Reconstruction with a smaller flap size has a higher possibility of fistula formation [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the current findings were consistent with their results. Sugiyama et al [ 16 ] reported that the use of an open drain, cardiovascular disease, and longer operation time are significant risk factors for abscess formation, fistula formation, and cervical flap necrosis. Reconstruction with a smaller flap size has a higher possibility of fistula formation [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…A history of radiation to the neck increases the risk of wound complications after head and neck surgery. 15 , 16 PLCE cannot prevent devascularization at the level of tracheostomy and tracheostomy; these areas are unavoidably located in the irradiated field when preoperative radiation is performed. These mechanisms may explain the association between preoperative chemoradiotherapy and a higher incidence of P‐TBN in PLCE.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the P-TBN-present group tended to have more frequent preoperative chemoradiotherapy and salvage surgery in PLCE. A history of radiation to the neck increases the risk of wound complications after head and neck surgery 15,16. PLCE cannot prevent devascularization at the level of tracheostomy and tracheostomy; these areas are unavoidably located in the irradiated field when preoperative radiation is performed.…”
mentioning
confidence: 99%
“…Although 1 patient developed anastomotic leakage caused by congested mucous membrane necrosis, the patient began oral intake on postoperative day 21 without symptoms of infection or inflammation. Sugiyama et al 1 reported that anastomotic leakage occurred in 11.3% of 773 Japanese patients. Our results were consistent with those reported, despite prior radiation therapy.…”
Section: Discussionmentioning
confidence: 99%
“…However, previous radiation therapy increases the risk of anastomotic leakage, which may lead to abscess formation, pharyngocutaneous fistula formation, and carotid rupture. 13 The mesenteric flap was first described by Nahai et al 4 This procedure is useful for covering the anastomotic site and obliterating dead space. However, the mesenteric flap is covered by a serosal membrane, which acts as a barrier to adhesion and vascularization between the flap and the surrounding tissue.…”
Section: Introductionmentioning
confidence: 99%